Mitochondrial function and sirtuin expression in hippocampus of young and old high- and low-capacity runner rats - Kontro, Hilkka (2016)
Introduction: Exercise and aerobic capacity are associated with improved learning in animals and humans. The hippocampus is a brain structure involved in learning and memory. High rates of neurogenesis have been shown to take place in the dental gyrus of hippocampus in response to physical exercise. It is not known whether mitochondrial dysfunction in the hippocampus is responsible for decline in cognitive function associated with low fitness level and aging, and whether intrinsic aerobic capacity is a risk factor for it. Methods: Mitochondrial function was investigated in the hippocampi of young and old highcapacity runner (HCR) and low-capacity runner (LCR) rats using high-performance respirometry. Mitochondrial sirtuins and total mitochondrial respiratory chain complexes were also quantified using Western blot. Results: Statistical analysis showed a significant difference in the LEAK respiration state (P<0.05) and LEAK control ratio (P<0.01) between young and old LCR rats (L: 8.83 ± 1.8 vs. 9.67 ± 1.92 pmol/s/mg and L/E: 0.083 ± 0.016 vs. 0.114 ± 0.025, respectively). A significant difference was found also between young HCR and old HCR rat OXPHOS (P) and ETS (E) states (P: 53.7 ± 5.6 vs. 47.0 ± 9.4 pmol/s/mg, E: 100.9 ± 17.6 vs. 83.3 ± 18.1 pmol/s/mg, respectively). No differences were found between young HCR and young LCR, or old HCR and old LCR. The correlation analysis showed a positive correlation between mitochondrial content and ETS (r = 0.32, P<0.05). Sirt4 was positively correlated with CII respiration (r = 0.35, P<0.05). ETS was positively correlated with all respiratory states, i.e. LEAK (r = 0.44), OXPHOS (r = 0.71), CI (r = 0.67), and CII (r = 0.44; P<0.01 for all), and negatively with the coupling control ratios L/E (r = -0.54) and P/E (r = -0.52; <0.01 for both). There was no correlation between CI and CII respiration, CII and L/E, LEAK and CII, or LEAK and P/E. Conclusions: LCR rats show an increased LEAK state respiration as they age, which may be related to mitochondrial dysfunction. However, we did not find a difference in their mitochondrial sirtuin levels or total mitochondrial content in the hippocampus compared to HCR to explain this finding. Even HCR show a decline in their OXPHOS and ETS capacity with age, but not in LEAK state respiration.